2017
DOI: 10.1007/s11356-017-0488-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mining activities on evolution of water quality of karst waters in Midwestern Guizhou, China: evidences from hydrochemistry and isotopic composition

Abstract: Zhijin coal-mining district, located in Midwestern Guizhou Province, has been extensively exploited for several decades. The discharge of acid mine drainage (AMD) has constituted a serious threat to local water environmental quality, which greatly affected the normal use of local people. The Permian limestone aquifer is the essential potable water supply for local people, which covered under the widely distributed coal seams. To investigate the origin of the water, the evolutionary processes, and the sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…As shown in the Fig. 5 , the δ 34 S in the of Youyu stream was between −5.68‰ and −8.23‰, with an average of −7.44‰, is mainly distributed near the coal end element and in the range of rivers polluted by Guizhou coal mines ( Cao et al, 2018 ; Li et al, 2018 ). Which indicates the SO 4 2 – ions in the river water are mainly affected by the coal mine wastewater.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As shown in the Fig. 5 , the δ 34 S in the of Youyu stream was between −5.68‰ and −8.23‰, with an average of −7.44‰, is mainly distributed near the coal end element and in the range of rivers polluted by Guizhou coal mines ( Cao et al, 2018 ; Li et al, 2018 ). Which indicates the SO 4 2 – ions in the river water are mainly affected by the coal mine wastewater.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, previous studies have shown that agricultural land and coal mines, municipal sewage, etc . may be natural sources of release of trace elements in the water environment ( Li et al, 2018 ; Njuguna et al, 2020 ; Wang et al, 2017 ). High concentrations of trace elements in the aquatic environment pose potential risks ( Zhan, Wu & Jin, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most prevalent forms of nitrogen pollution in WWTP, NH 4 + originated primarily from wastewater plant discharges, the same source of antibiotics. SO 4 2− is mainly derived from both natural (dissolution of soluble sulfate, oxidation of sulfide minerals, and atmospheric precipitation) and anthropogenic inputs(agricultural fertilizers, domestic sewage, industrial wastewater, and mine waste water) (Li et al, 2018). In the study area, the [Mg 2+ ]/[Ca 2+ ] values ranged from 0.39 to 1.14 with average 0.65, which indicated that the chemical composition is mainly influenced by low-magnesium minerals such as calcite and gypsum.…”
Section: Characteristics Of Physicochemical Properties Of Karst Rivermentioning
confidence: 99%
“…The karst area has a complex geological structure, widespread faults and caves, and rich mineral resources, and the karst groundwater system is extremely sensitive to tunnel construction. Although some scholars have studied the hydrogeochemical processes induced by mining activities in the karst areas of Southwest China [15,16], however, there are no reports on groundwater chemistry in the karst tunnel fracture zone; the existing research on groundwater related to tunnel mainly focuses on the influence of groundwater level decline and water pressure on the safety of lining structure, lack of understanding of groundwater and surrounding rock matrix water-rock interaction. As a result, it is critical to conduct groundwater chemical processes and water quality research for karst tunnels.…”
Section: Introductionmentioning
confidence: 99%